A biomechanical comparison of single-leg landing and unplanned sidestepping - Chinnasee, C.; Weir, G.; Sasimontonkul, S.; Alderson, J.; Donnelly, C. (International Journal of Sports Medicine, 2018)
Unplanned sidestepping and single-leg landing have both been used to screen athletes for injury risk in sport. The aim of this study was to directly compare the lower limb mechanics of three single-leg landing tasks and an unplanned sidestepping task. Thirteen elite female team sport athletes completed a series of non-contact single-leg drop landings, single-leg countermovement jumps, single-leg jump landings and unplanned sidestepping in a randomized counterbalanced design. Three dimensional kinematics (250 Hz) and ground reaction force (2,000 Hz) data with a participant specific lower limb skeletal model were used to calculate and compare hip, knee and ankle joint kinematics, peak joint moments, instantaneous joint power and joint work during the weight acceptance phase of each sporting task (a=0.05). Peak knee joint moments and relevant injury risk thresholds were used to classify each athlete's anterior cruciate ligament injury risk during unplanned sidestepping and single-leg jump landing. Results showed that peak joint moments, power and work were greater during the single-leg jump landing task when compared to the single-leg drop landings and single-leg countermovement jumps tasks. Peak frontal and sagittal plane knee joint moments, knee joint power, as well as hip and knee joint work were greater during unplanned sidestepping when compared to the landing tasks. Peak ankle joint moments, power and work were greater during the landing tasks when compared to unplanned sidestepping. For 4 of the 13 athletes tested, their anterior cruciate ligament injury risk classification changed depending on whether they performed an unplanned sidestepping or single-leg jump landing testing procedure. To summarize, a single-leg jump landing testing procedure places a larger mechanical on the ankle joint when compared to single-leg drop landings, single-leg countermovement jumps and unplanned sidestepping. An unplanned sidestepping testing procedure places a larger mechanical demand on the knee joint when compared to single-leg landing tasks. Both unplanned sidestepping and single-leg jump landing testing procedures are recommended for classifying an athlete's anterior cruciate ligament injury risk in sport.